Nova proposta didática para o ensino de biologia molecular na educação básica - Silva, Marilia Faustino da (Universidade Federal de São Carlos, 2022)
The teaching of science and biology in basic education aims to provide minimum content so that individuals can deal with new information and are able to understand, question and position themselves in the face of ethical debates arising from the development and applications in the area of Biotechnology and Molecular Biology. However, the flow of information generated is not accompanied by the dissemination of scientific information in the school environment, nor is it incorporated into teaching knowledge on a continuous basis. In addition, the teaching of Molecular Biology and its related concepts, which involve a great capacity for abstraction on the part of the students, requires the elaboration and use of specific teaching resources. In this context, this work aimed to organize, develop and implement a continuing education course offered to teachers in basic education, focusing on the teaching profile of the public network, their needs and difficulties related to the teaching of Molecular Biology. From these data, a gamified software called BIOQUEST was developed, aimed at high school students. Then, the usability of the software and the impact on the learning of concepts related to Molecular Biology were evaluated, comparing the results of a conceptual test with students who used the BIOQUEST software, and students who had contact with the concepts in the traditional way. education. Data analysis based on the use of BIOQUEST revealed that , the software can be used as a pedagogical resource with basic education students, since it presents the concepts related to Molecular Biology in a playful way, being well evaluated in relation to usability. , exploration of the game in its entirety, the relevance of the subject for learning and ease of manipulation and navigation in the game, in addition to having a positive impact on the learning of concepts.
New didactic proposal for teaching molecular biology in basic education
Keywords: Educação básica; Basic education; Formação de professores; Teacher training; Ensino; Teaching; Biologia molecular; Molecular biology; Software gamificado; Gamified software; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR